Complexome profiling on the Chlamydomonas lpa2 mutant reveals insights into PSII biogenesis and new PSII associated proteins. (26th August 2021) - Spaniol, Benjamin; Lang, Julia; Venn, Benedikt; Schake, Lara; Sommer, Frederik; Mustas, Matthieu; Geimer, Stefan; Wollman, Francis-André; Choquet, Yves; Mühlhaus, Timo; Schroda, Michael
Abstract : We identify three novel proteins potentially associated with PSII and a role for auxiliary factor LPA2 in catalysing a step required for stable PSII assembly beyond PSII monomers in Chlamydomonas . Abstract: While the composition and function of the major thylakoid membrane complexes are well understood, comparatively little is known about their biogenesis. The goal of this work was to shed more light on the role of auxiliary factors in the biogenesis of photosystem II (PSII). Here we have identified the homolog of LOW PSII ACCUMULATION 2 (LPA2) in Chlamydomonas . A Chlamydomonas reinhardtii lpa2 mutant grew slower in low light, was hypersensitive to high light, and exhibited aberrant structures in thylakoid membrane stacks. Chlorophyll fluorescence ( F v / F m ) was reduced by 38%. Synthesis and stability of newly made PSII core subunits D1, D2, CP43, and CP47 were not impaired. However, complexome profiling revealed that in the mutant CP43 was reduced to 23% and D1, D2, and CP47 to 30% of wild type levels. Levels of PSI and the cytochrome b 6 f complex were unchanged, while levels of the ATP synthase were increased by 29%. PSII supercomplexes, dimers, and monomers were reduced to 7%, 26%, and 60% of wild type levels, while RC47 was increased 6-fold and LHCII by 27%. We propose that LPA2 catalyses a step during PSII assembly without which PSII monomers and further assemblies become unstable and prone to degradation. The LHCI antenna was more disconnected from PSI in the lpa2 mutant, presumably as an adaptive response to reduce excitation of PSI. From the co-migration profiles of 1734 membrane-associated proteins, we identified three novel putative PSII associated proteins with potential roles in regulating PSII complex dynamics, assembly, and chlorophyll breakdown.